PENINGKATAN HASIL BELAJAR PPKn DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS IV SD NEGERI 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Achmad Ikrom (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Based on the author’s teaching experience at SD Negeri 010 Banjar Panjang, supported by initial observations and reflections, it was found that students’ creativity in learning was relatively low, which ultimately had an impact on their low learning outcomes, particularly in Civics (PPKn). This condition was further evidenced by the results of the midterm assessment, which showed that students’ learning outcomes were still below expectations. Classical mastery reached only 50%, meaning that only 20 out of 40 students achieved the minimum mastery criterion (KKM) of 70 set for PPKn in Grade IV at SD Negeri 010 Banjar Panjang. The purpose of this research was to improve students’ PPKn learning outcomes through the implementation of the demonstration method. This study employed a classroom action research (PTK) design, which was conducted through the stages of planning, implementation, observation, and reflection. The research was carried out at SD Negeri 010 Banjar Panjang in April 2016, with fourth-grade students as the research subjects. The results of the actions taken indicate a significant improvement in students’ PPKn learning outcomes from the preliminary data through Cycle I and Cycle II. In the preliminary stage, only 50% of students achieved mastery learning. After the implementation of actions in Cycle I, learning mastery increased to 70%, and in Cycle II, classical mastery further improved to 85%. These findings demonstrate that the application of the demonstration method effectively enhances students’ creativity and learning outcomes in PPKn for fourth-grade students at SD Negeri 010 Banjar Panjang.